RELATIONSHIP BETWEEN PERIODONTAL DISEASES AND PREECLAMPSIA: A WARNING FOR ORAL HEALTH DURING PREGNANCY - dos Santos, Pedro Guimarães Sampaio Trajano; Lopes, Daniela Siqueira; Silva, Ana Paula de Medeiros; do Nascimento, Alexandre Batista Lopes; Rodrigues, Verônica Maria de Sá; Cavalcanti, Maria Tereza Moura de Oliveira; de Souza, Gleicy Fátima Medeiros; de Menezes, Maria Regina Almeida; Chaves, Adriane Tenório Dourado; de Araujo, Luciane Farias; Travassos, Rosana Maria Coelho; Silva, Luciano Barreto (ARACÊ, 2025)
Objective: The objective of this narrative literature review is to address the relationship between periodontal disease in pregnant women and its correlation with the risk of acquiring preeclampsia. Methodology: During the development of the article, it became evident that there was a need to acquire as much relevant information related to the topic as possible, articles, research and other tested, proven and published studies, serving as a source of support and enrichment for the review. Thus, research was done in the following databases: PubMed; Scielo; The Cochrane Library; Science Direct; PROSPERO in conjunction with Google Academy. Results: Preeclampsia is a serious disorder that can cause deterioration of several organs in different systems, which is the cause of maternal death in the vast majority of cases, in addition to being able to lead to fetal death. Many studies indicate the correlation of periodontal disease in pregnant women as a factor that favors the development of this disorder, through the concept that inflammation may be associated with the etiology and pathology of preeclampsia in the following ways: through the increased risk of uteroplacental atherosclerosis and through the possibility of potentiating the systemic inflammatory response. Conclusion: Several studies indicate the relationship between periodontal disease and preeclampsia, however, more research and studies on the subject are needed.